CUSTOMER SATISFACTION ON E-BANKING SERVICES WITH REFERENCE TO SBI, BENGALURU CITY - Gopinath, Mr. C B; Mr. T Sivakumar,; Mr. Murali .V, (The journal of contemporary issues in business and government, 2022)
E-Banking is your personal banking service on the Internet, protected with bank identifiers. It isavailable anywhere, anytime. E-Banking allows you to pay invoicesto Finnish andforeignrecipients easily and securely. 150 respondents wereselected and met in thestudy. As regards data collection, a standard Questionnaire withquestions was prepared by theresearcherand given to thecustomers ofSBIbranches in Bengaluru city. This study iscarried for a period of 12 months from April 2021 to March 2022. Study finds that there are significant relationships between Age, Qualifications, Income, and usage of e-banking and overall satisfaction of the e-banking. In Anova analysis finds that there is no significant difference in performance, services and age of the customers.